Islamic Education in Shaping a Civilized Generation amid the Dynamics of Globalization: (Pendidikan Islam Dalam Membentuk Generasi Beradab Di Tengah Dinamika Globalisasi) - Azrianti Ishamiyah; Konto Iskandar Dinata; Muhammad Mirzan (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
The role of Islamic education in forming a civilized generation amidst globalization. Globalization brings significant challenges to the younger generation, such as the influence of foreign cultures and moral crises. Islamic education, with a focus on the values of monotheism, morals and manners, is expected to be a solution in facing this challenge. Through a holistic approach involving family, school and community, as well as the use of technology, Islamic education can strengthen the character of the younger generation. This research uses qualitative methods with literature study to analyze the relevance of Islamic education in a global context. The results show that the integration of Islamic values in modern education is very important to create individuals who are intelligent, have morals, and are able to compete globally